Knowledge of physiotherapists about the treatment of peripheral facial palsy (Research, Society and Development, 2022)
Peripheral facial palsy is a type of pathology arising from a lesion in the seventh cranial nerve, the Facial. Due to recent changes in the treatment of peripheral facial paralysis, it is extremely important that physical therapists are aware of the new techniques used for the treatment and those that have become obsolete and without scientific evidence. Therefore, the present study aims to investigate the knowledge of physical therapists about the treatment of peripheral facial paralysis. This is a cross-sectional, descriptive study with a quantitative approach, with descriptive data analysis. The study population consisted of 74 physical therapists who are active in the national territory, regardless of age, of both sexes and who care for patients with facial palsy or not. Data were collected through an online form. The results showed that physical therapists are not up to date on the techniques for rehabilitation of a patient with Peripheral Facial Palsy. It is concluded that physical therapists do not have knowledge about updates on the treatment of peripheral facial paralysis.